Crosssampler: A Digital Convolution Cross Synthesis Instrument - Eadie, Jimmy (My University, 2024)
Convolutional Cross Synthesis (CCS) has emerged as a powerful technique for blending input signals to create hybrid sounds. It has significantly expanded the horizons of digital signal processing, enabling artists to explore novel audio effects. However, the conventional applications of CCS primarily revolve around reverberation and room simulation, rather than being utilized as a creative synthesis method. In this paper, we present the design of a digital instrument CrossSampler that harnesses a parametric approach to convolution cross synthesis which involves using adjustable parameters to control the blending of audio signals through convolution. These parameters allow for customization of the resulting sound, offering greater creative control and flexibility. It enables users to shape the output by manipulating factors such as duration, intensity, and spectral characteristics. This approach facilitates experimentation and exploration in sound design and opens new sonic possibilities.
Journal of Electronics and Communication Engineering
ICASPMA 2024: 18. Audio Signal Processing for Music Applications
PUBLISHED
Paris, France
Keywords: Convolution, Synthesis, Sampling, Virtual Instrument